2016
DOI: 10.1103/physrevlett.116.136802
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Power in Graphene: Violation of the Mott Relation by Inelastic Scattering

Abstract: We report the enhancement of the thermoelectric power (TEP) in graphene with extremely low disorder. At high temperature we observe that the TEP is substantially larger than the prediction of the Mott relation, approaching to the hydrodynamic limit due to strong inelastic scattering among the charge carriers. However, closer to room temperature the inelastic carrier-optical-phonon scattering becomes more significant and limits the TEP below the hydrodynamic prediction. We support our observation by employing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
199
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(213 citation statements)
references
References 45 publications
13
199
1
Order By: Relevance
“…Enhancement of S by inelastic scattering has been reported recently by Ghahari et al [18]. Experimental electrical conductivity studies of graphene doped with potassium as a function of charge carrier has been reported by Chen et al [11].…”
Section: Impurity Scattering In Graphenementioning
confidence: 87%
See 2 more Smart Citations
“…Enhancement of S by inelastic scattering has been reported recently by Ghahari et al [18]. Experimental electrical conductivity studies of graphene doped with potassium as a function of charge carrier has been reported by Chen et al [11].…”
Section: Impurity Scattering In Graphenementioning
confidence: 87%
“…A further motivation to study the effects of impurity scattering on graphene sheets was provided by a recent paper by Ghahari et al [18], which reported an enhanced Seebeck coefficient in graphene due to scattering. We have used a tight-binding model (TBM) for graphene with impurities and solved the Boltzmann transport equations for electrons to study the effect of impurities on electrical conductance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works show that graphene is a good thermoelectric material with a moderate Seebeck coefficient 10,11 . Though, due to its high thermal conductance, it possesses a very small thermoelectric figure of merit ZT around 0.1-0.001, much smaller than the most efficient 3D thermoelectric material Bi 2 Te 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In the calculation, inelastic electronphonon interaction is not included because the screened Coulomb scattering is dominant in this temperature range as indicated by the energy scale of the RPF. However, electron-phonon scattering could become important when the temperature yields a k B T that is much higher than the energy of RPF as in the case for hBN-encapsulated graphene devices (43).…”
Section: ·Kmentioning
confidence: 99%